The relationship between consumer price index (CPI) and producer price index (PPI) in Malaysia - Then, Linda Wee Mei (Universiti Malaysia Sarawak (UNIMAS), 2011)
The purpose of this research is to investigate that the relationship between producer price index (PPI) and consumer price index (CP1) in Malaysia. In contrast with previous studies, many information of the PPI to be useful forecasts improve to the CPI. The research use monthly data of consumer price index (CPO and producer price index (PPI) from period January 1986 to December 20 1~ The unit root test and Johansen co integration test is used to investigate the transfer of change from consumer price index and producer price index, or in other words to test the existence or not of a long-term relationship between the two variables. Granger Causality test to find that there is uni-directional or bi-directional causality between the PPI and CPI. The result shown that policy makers to rely more on the link to between CPI and PPI and use changes in PPI to predict changes in CPI.